PERHITUNGAN TARIF SEWA GEDUNG VIDYA LOKA DENGAN METODE COST PLUS PRICING PENDEKATAN FULL COSTING - Lusi Mei Cahya W; Wilhelmina Putri N (JISO : Journal of Industrial and Systems Optimization, 2021)
The Vidya Loka building at Darma Cendika Catholic University (UKDC) has several rooms that can be rented by the general public, namely Serbaguna room (2nd floor), Seminar Timur room and Seminar Barat room (3nd floor)  starting October 2019. Determination of current rental fees is only based on price competitors around Surabaya. This study aims to provide input to managers building regarding the calculation of rental costs using the Cost Plus Pricing method with Full Costing approach that considers long term benefits. The result of calculating rental fees based on data for 3 months, December 2019 – February 2020 show there is a large difference, especially for the Seminar room. Through the calculation of Full Costing with an expected profit of 30% of operational costs, the rental rate is obtained per 6 hours as follows : Serbaguna room IDR 5,300,000, Seminar Timur room IDR 450,000 and Seminar Barat room  IDR 700,000